This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MATH 20C Lecture 16  Monday, November 1, 2010 Implicit differentiation Example: x 2 + yz + z 3 = 8 . Viewing z = z ( x,y ) , compute z x and z y . Take x of both sides of x 2 + yz + z 3 = 8 . Get 2 x + y z x +3 z 2 z x = 0 , hence z x = 2 x y +3 z 2 = 2 3 . In general, consider a surface F ( x,y,z ) = c. The we can view z = z ( x,y ) as a function of two independent variables x,y and compute z x and z y . To do so, we take the partial derivative with respect to x of both sides of the equation F ( x,y,z ) = c and get (by the chain rule) F x x x + F y y x + F z z x = 0 . But x/x = 1 and, since x and y are independent, y/x = 0 (changing x does not affect y ). Hence the equation above really says that F x + F z z x = 0 which implies z x = F x F z . Similarly, z y = F y F z . Changing gears, lets see how we can recover f from its gradient. Say f = h 3 x 2 y,x 3 +2 z, 2 y + cos z i . We proceed by successive integration. We are given that f x = 3 x 2 y. Integrating with respect to x (view y,z as constants), we see that f = x 3 y + g ( y,z ) . Therefore f y = x 3 + g y . But we know from the gradient that f y = x 3 + 2 z , hence g y = 2 z. Integrate with respect to y and get g = 2 yz + h ( z ) , hence f = x 3 y + 2 yz + h ( z ) . Since f z = 2 y + cos z we get that dh dz = cos z, so h ( z ) = sin z + C. Substituting in the expression of f gives f = x 3 y + 2 yz + sin z + C....
View
Full
Document
 Spring '08
 Helton
 Math

Click to edit the document details